2009
DOI: 10.1002/cssc.200800248
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalysed Direct 3‐ or 4‐Arylation of 2,5‐Disubstituted Pyrrole Derivatives: An Economically and Environmentally Attractive Procedure

Abstract: Straight to the point: The direct 3- or 4-arylation of pyrrole derivatives through C--H bond activation proceeds in moderate to good yields using Pd(OAc)(2) as catalyst. In contrast to classical coupling procedures, the preparation of an organometallic derivative is not required and the major by-products are AcOH/KBr instead of metallic salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…[6] This type of methodology presents the advantage of circumventing the preparation of organometallic nucleophilic reagents. It also avoids stoichiometric formation of metallic side products, from which undesired contamination could be appalling for pharmaceutical, agrochemical, and related biological applications.Reports of palladium-catalyzed direct arylations of heteroaromatics have described the use of organic bromides, [7] iodides, [8] triflates, [9] mesylates and tosylates, [10] sulfamates and phosphates, [11] iodonium salts, [12] and potassium trifluoroborates [13] as useful reagents. Organic chlorides remained noticeably uncommon partners, [14] despite the fact that among halides and pseudohalides, chlorides are arguably the most useful single class of substrates because of their straightforward access, their lower cost, and the wider diversity of available compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6] This type of methodology presents the advantage of circumventing the preparation of organometallic nucleophilic reagents. It also avoids stoichiometric formation of metallic side products, from which undesired contamination could be appalling for pharmaceutical, agrochemical, and related biological applications.Reports of palladium-catalyzed direct arylations of heteroaromatics have described the use of organic bromides, [7] iodides, [8] triflates, [9] mesylates and tosylates, [10] sulfamates and phosphates, [11] iodonium salts, [12] and potassium trifluoroborates [13] as useful reagents. Organic chlorides remained noticeably uncommon partners, [14] despite the fact that among halides and pseudohalides, chlorides are arguably the most useful single class of substrates because of their straightforward access, their lower cost, and the wider diversity of available compounds.…”
mentioning
confidence: 99%
“…The intermolecular palladium-catalyzed direct arylation of pyrroles using chloroarenes is of interest, [17c] and mostly intramolecular cyclizations [17a] or reactions using heteroaryl chlorides [14a] have been reported. We observed that the coupling of 1-methyl-2-formylpyrrole with several chloroarenes selectively gives the desired coupling products 19 a-19 g in excellent to fairly good yields ( Table 4, entries [4][5][6][7][8]. Electron-deficient para-, meta-, or ortho-substituted chloroarenes displaying important functional groups can be employed.…”
mentioning
confidence: 99%
“…[145] In 2009, Fall, Doucet and Santelli demonstrated that b-arylation of 1,5-dimethyl-2-pyrrolecarbonitrile (211b), 1,2,5-trimethylpyrrole (211a) and 2,5-dimethyl-1-phenylpyrrole (211c) could be achieved by treatment of these heteroarenes with functionalized (hetero)aryl bromides in DMA at 130 8C in the presence of KOAc as the base and a catalytic amount of PdA C H T U N G T R E N N U N G (OAc) 2 (Scheme 111). [146] The resulting coupling products were generally obtained in moderate to good yields but the reaction between 211b and 4-bromoanisole did not give the expected arylation product. Interestingly, the reaction conditions used to prepare compounds 212a-c proved also suitable for the C-3 arylation of 2,5-dimethylpyrrole (213) with electron-deficient aryl bromides (Scheme 112).…”
Section: Scheme 101 a C H T U N G T R E N N U N G [Rucl 2 A C H T U mentioning
confidence: 98%
“…Interestingly, the reaction conditions used to prepare compounds 212a-c proved also suitable for the C-3 arylation of 2,5-dimethylpyrrole (213) with electron-deficient aryl bromides (Scheme 112). [146] In 2011, Yorimitsu, Osuka and co-workers developed a method for the Pd-catalyzed direct b-selective arylation of porphyrins with aryl bromides. [147] The approach, which involved treatment of Ni(II) complex 214 of 5,10,15-tris(3,5-di-tert-butylphenyl)porphyrin with 10 equiv.…”
Section: Scheme 101 a C H T U N G T R E N N U N G [Rucl 2 A C H T U mentioning
confidence: 99%
“…Unlike the numerous examples of Pd‐catalyzed intermolecular direct α‐arylations of pyrroles with (hetero)aryl halides, only a few Pd‐catalyzed intermolecular β‐arylations have been reported in the literature 145. In 2009, Fall, Doucet and Santelli demonstrated that β‐arylation of 1,5‐dimethyl‐2‐pyrrolecarbonitrile ( 211b ), 1,2,5‐trimethylpyrrole ( 211a ) and 2,5‐dimethyl‐1‐phenylpyrrole ( 211c ) could be achieved by treatment of these heteroarenes with functionalized (hetero)aryl bromides in DMA at 130 °C in the presence of KOAc as the base and a catalytic amount of Pd(OAc) 2 (Scheme ) 146…”
Section: Intermolecular Direct (Hetero)arylation Of Five‐membered Hmentioning
confidence: 99%